Remotely monitored therapy and nitric oxide suppression identifies nonadherence in severe asthma - Heaney, LG; Busby, J; Bradding, P; Chaudhuri, R; Mansur, AH; Niven, R; Pavord, I; Lindsay, JT; Costello, RW (American Thoracic Society, 2018)
Rationale: Poor adherence is common in difficult-to-control asthma. Distinguishing patients with difficult-to-control asthma who respond to inhaled corticosteroids (ICS) from refractory asthma is an important clinical challenge. Objectives: Suppression of fractional exhaled nitric oxide (FeNO) with directly observed ICS therapy over 7 days can identify nonadherence to ICS treatment in difficult-to-control asthma. We examined the feasibility and utility of FeNO suppression testing in routine clinical care within UK severe asthma centers using remote monitoring technologies. Methods: A web-based interface with integrated remote monitoring technology was developed to deliver FeNO suppression testing. We examined the utility of FeNO suppression testing to demonstrate ICS responsiveness and clinical benefit on electronically monitored treatment with standard high-dose ICS and long-acting β2-agonist treatment. Measurements and Main Results: Clinical response was assessed using the Asthma Control Questionnaire-5, spirometry, and biomarker measurements (FeNO and peripheral blood eosinophil count). Of 250 subjects, 201 completed the test with 130 positive suppression tests. Compared with a negative suppression test, a positive test identified a FeNO-low population when adherent with ICS/long-acting β2-agonist (median, 26 ppb [interquartile range, 16–36 ppb] vs. 43 ppb [interquartile range, 38–73 ppb]) with significantly greater FEV1% (mean, 88.2 ± 16.4 vs. 74.1 ± 20.9; P < 0.01). Asthma Control Questionnaire-5 improved significantly in both groups (positive test: mean difference, −1.2; 95% confidence interval, −0.9 to −1.5; negative test: mean difference, −0.9; 95% confidence interval, −0.4 to −1.3). Conclusions: Remote FeNO suppression testing is an effective means of identifying nonadherence to ICS in subjects with difficult-to-control asthma and the substantial population of subjects who derive important clinical benefits from optimized ICS/long-acting β2-agonist treatment.